2014
DOI: 10.1155/2014/901315
|View full text |Cite
|
Sign up to set email alerts
|

Toona sinensisInhibits LPS-Induced Inflammation and Migration in Vascular Smooth Muscle Cells via Suppression of Reactive Oxygen Species and NF-κB Signaling Pathway

Abstract: Toona sinensis is one of the most popular vegetarian cuisines in Taiwan and it has been shown to possess antioxidant, antiangiogenic, and anticancer properties. In this study, we investigated the antiatherosclerotic potential of aqueous leaf extracts from Toona sinensis (TS; 25–100 μg/mL) and its major bioactive compound, gallic acid (GA; 5 μg/mL), in LPS-treated rat aortic smooth muscle (A7r5) cells. We found that pretreatment with noncytotoxic concentrations of TS and GA significantly inhibited inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 51 publications
(74 reference statements)
1
20
0
Order By: Relevance
“…Later in 2012, a report demonstrated that total polyphenols from the seeds of T. sinensis (TPST) had therapeutic effects on adjuvant-induced arthritis rats (Yang and Chen, 2012). Furthermore, using NF-B transgenic mice and bioluminescence imaging, another two investigations revealed that TSL and gallic acid could inhibit LPS-induced inflammation via suppressing NF-B pathway in vivo and in vitro (Hsiang et al, 2013;Yang et al, 2014). Recently, Chen et al (2017) reported that the 7deacetylgedunin (13) isolated form the T. sinensis suppresses LPS induced inflammatory responses in RAW264.7 cells through activating Keap1/Nrf2/HO-1 pathway.…”
Section: Anti-inflammatory Effectmentioning
confidence: 99%
“…Later in 2012, a report demonstrated that total polyphenols from the seeds of T. sinensis (TPST) had therapeutic effects on adjuvant-induced arthritis rats (Yang and Chen, 2012). Furthermore, using NF-B transgenic mice and bioluminescence imaging, another two investigations revealed that TSL and gallic acid could inhibit LPS-induced inflammation via suppressing NF-B pathway in vivo and in vitro (Hsiang et al, 2013;Yang et al, 2014). Recently, Chen et al (2017) reported that the 7deacetylgedunin (13) isolated form the T. sinensis suppresses LPS induced inflammatory responses in RAW264.7 cells through activating Keap1/Nrf2/HO-1 pathway.…”
Section: Anti-inflammatory Effectmentioning
confidence: 99%
“…Fermentation by Lactobacillus potentiates the anti-inflammatory effect of Oyaksungisan by inhibiting NF-κB and MAPKs' activity in LPSstimulated RAW 264.7 mouse macrophage cells (Oh et al, 2012). Toona sinensis inhibits the NF-κB activation and MAPKs' phosphorylation in LPS-induced vascular smooth muscle cell inflammation (Yang et al, 2014). However, prior to the present study it was unknown whether MAPKs are the targets of SH during the inhibition of LPS-induced bEECs inflammation.…”
Section: Discussionmentioning
confidence: 75%
“…Moreover, Liu et al (2014a) found that supplementation with quercetin, which is well known for rich phenolic components and high antioxidant effects, could increase chickens' SOD activity. Yang et al (2014a) showed that aqueous extracts of TS improved functions of sperm and testes for male rats under oxidative stress. In this study, high antioxidant activity of TS could better increase the serum SOD content than the control group in the 0.2% TS group; hence, it may suggest that natural secondary metabolites found in the aforementioned extracts affect gene expression of antioxidant enzymes (Puiggross et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The major breed of meat geese in Taiwan is the White Roman goose, which represents 97.0% of the market product, the other 3% is provided by Chinese goose. As food/feed safety and animal welfare concerns continue to improve, researchers seek better antibiotic alternatives for domestic geese than those currently used (Yang et al 2014a). …”
Section: Introductionmentioning
confidence: 99%